(untitled) (KULT_online, 2019)
This 2017 monograph by Martin Camper, Arguing over Texts. The Rhetoric of Interpretation, presents a method to structure and analyze the process of talking and arguing over texts based on the classical concept of stasis and expands it, combining rhetoric and twentieth-century linguistics. The book is an entertaining journey that travels through each stasis, illustrating them with examples from multiple fields, and updates a topic that can be seen as distant but holds great importance in the contemporary world.